Raman–Mössbauer–XRD studies of selected samples from "Los Azulejos" outcrop: A possible analogue for assessing the alteration processes on Mars. Issue 11 (1st June 2016) - Lalla, E.A.; Sanz-Arranz, A.; Lopez-Reyes, G.; Sansano, A.; Medina, J.; Schmanke, D.; Klingelhoefer, G.; Rodríguez-Losada, J.A.; Martínez-Frías, J.; Rull, F.
Abstract: The outcrop of "Los Azulejos" is visible at the interior of the Cañadas Caldera in Tenerife Island (Spain). It exhibits a great variety of alteration processes that could be considered as terrestrial analogue for several geological processes on Mars. This outcrop is particularly interesting due to the content of clays, zeolite, iron oxides, and sulfates corresponding to a hydrothermal alteration catalogued as "Azulejos" type alteration. A detailed analysis by portable and laboratory Raman systems as well as other different techniques such as X-ray diffraction (XRD) and Mössbauer spectroscopy has been carried out (using twin-instruments from Martian lander missions: Mössbauer spectrometer MIMOS-II from the NASA-MER mission of 2001 and the XRD diffractometer from the NASA-MSL Curiosity mission of 2012). The mineral identification presents the following mineral species: magnetite, goethite, hematite, anatase, rutile, quartz, gregoryite, sulfate (thenardite and hexahydrite), diopside, feldspar, analcime, kaolinite and muscovite. Moreover, the in-situ Raman and Micro-Raman measurements have been performed in order to compare the capabilities of the portable system specially focused for the next ESA Exo-Mars mission. The mineral detection confirms the sub-aerial alteration on the surface and the hydrothermal processes by the volcanic fluid circulations in the fresh part. Therefore, the secondary more abundant mineralization acts as the color agent of the rocks. Thus, the zeolite–illite group is the responsible for the bluish coloration, as well as the feldspars and carbonates for the whitish and the iron oxide for the redish parts. The XRD system was capable to detect a minor proportion of pyroxene, which is not visible by Raman and Mössbauer spectroscopy due to the "Azulejos" alteration of the parent material on the outcrop. On the other hand, Mössbauer spectroscopy was capable of detecting different types of iron-oxides (Fe 3+/2+ -oxide phases). These analyses emphasize the strength of the different techniques and the working synergy of the three different techniques together for planetary space missions.